2020
DOI: 10.3390/foods9030334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boswellia Serrata and Whey Protein Powders on Physicochemical Properties of Pork Patties

Abstract: Processed meat products are prone to oxidative damage and quality decline during storage; however, these problems can be mitigated by the proper formulation of meat productions. This study evaluated the effects of natural anti-oxidants found in Boswellia serrata (B), whey protein powder (W), and their combination on pork patties during storage, exploring changes in textural properties and lipid oxidation susceptibility. The 2% whey-added group exhibited a higher crude protein content than the untreated control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
(55 reference statements)
0
5
0
5
Order By: Relevance
“…Although significant progress has been made in managing synthetic drugs for cardiovascular diseases, the search for indigenous cardioprotective agents is continuing. It has been shown that at least 30 food spices and herbs possess antioxidant properties such as Boswellia serrata , Nigella sativa, saffron and their major components such as thymoquinone, and safranol, [ [18] , [19] , [20] , [21] ]. Curcumin, the major yellow bioactive component of turmeric ( Curcuma longa L., Zingiberaceae), is a more recent discovery [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although significant progress has been made in managing synthetic drugs for cardiovascular diseases, the search for indigenous cardioprotective agents is continuing. It has been shown that at least 30 food spices and herbs possess antioxidant properties such as Boswellia serrata , Nigella sativa, saffron and their major components such as thymoquinone, and safranol, [ [18] , [19] , [20] , [21] ]. Curcumin, the major yellow bioactive component of turmeric ( Curcuma longa L., Zingiberaceae), is a more recent discovery [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five batches of twenty patties each were prepared by adding salt, cysteine, B. serrata, and whey powder to the meat according to the formulations listed in Table 1. Combined with previously published paper [26], it was reported that the addition of B. serrata is set at 1% since the high concentration group has better water holding capacity and antioxidant effect. The level of cysteine was based on Majcher and Jelen [27], who stated that the addition of 0.25% result in the form of a pleasant aroma compared to other concentrations.…”
Section: Pork Patty Formulation and Processingmentioning
confidence: 68%
“…As proteínas presentes no soro são de alta qualidade, contendo aminoácidos essenciais e de alta digestibilidade, biologicamente superior a outras fontes proteicas. Estudos mostraram que essas proteínas promovem grandes benefícios a saúde, como atividade antioxidante, regulação imunológica e propriedades antibacterianas e anticâncer (YANG et al, 2020). fermentados tradicionalmente caseiros, em condições industriais.…”
Section: Carne E Derivados E Sua Importância Para Alimentaçãounclassified
“…O soro possui propriedades e componentes que apresentam atividades antioxidantes. Os consumidores geralmente tem a tendencia de preferir antioxidantes naturais, e uma outra grande vantagem é que esses aditivos conseguem manter a umidade, os lipídios e a composição dos alimentos, bem como melhorar o sabor, tudo isso necessário para embutidos (YANG et al, 2020).…”
Section: Carne E Derivados E Sua Importância Para Alimentaçãounclassified
See 1 more Smart Citation